The technical efficiency of country responses to the COVID-19 pandemic - Desjardins, Armand (niversity of the Witwatersrand, Johannesburg, 2023)
The COVID-19 pandemic saw the most comprehensive implementation in history of pharmaceutical and non-pharmaceutical interventions by governments around the world. A better understanding of how efficient these interventions are, especially given their high economic costs to society is pivotal in designing similar policy for future outbreaks of this nature. This research estimates the technical efficiency of country responses to the COVID-19 pandemic using a Stochastic Frontier Analysis model and panel dataset combining indicators from the Our World in Data (OWID), Google Movement Index and World Bank Economic Indicators databases. The SFA regression also corrects for endogeneity in the input variables, as policy stringency tends to be influenced by the number of cases in each country. To do so, the OWID stringency index is used as an instrumental variable for each of the policy inputs to correct for the endogenous relationship between the input and output variables. The study found that the correction of technical efficiency estimates for endogeneity using the xtsfkk routine in Stata was an appropriate estimation strategy. The exogenously and endogenously estimated efficiency scores furthermore differed statistically significantly, with exogenously estimated scores representing overestimates of technical efficiency. Vaccination policies proved to be the most technically efficient channel of prevention followed by stay-at-home restrictions. A second stage OLS regression was used to estimate the effects of selected drivers on the technical efficiency scores computed in the Stage 1 SFA model. Health expenditure as a % of GDP, hospital beds per 1,000 population, and physicians per 1,000 population were all positively related to technical efficiency. Countries with reactive and flexible policy approaches, able to increase policy intensity levels based on COVID-19 waves, were found to obtain higher technical efficiency scores than wealthy countries. Improvements in the level of detail on the drivers of technical efficiency and the adoption of machine learning techniques to estimate efficiency scores are recommended to extend research in this area past its current scope
A Research Report submitted in partial fulfilment of the Degree of Master of Commerce (Health Economics) in the School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2023
Keywords: COVID-19 pandemic; Technical efficiency; Our World in Data; Google Movement Index; UCTD; SDG-3: Good health and well-being